Short Films as a Means of Education and Digital Marketing in Reviving the Entrepreneurial Spirit of the Young Buddhist Generation - Tri Yatno; Situ Asih; Agus Subandi; Ngadat Ngadat; Santi Paramita; Mugiyo Mugiyo (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
Making short films is part of a community service program for the young generation of Wonogiri Regency. This program aims to foster a spirit of change in education and creativity in digital marketing, especially regarding activities and institutions characterised by Buddhism in the Wonogiri Regency. This method of community service uses asset-based community development techniques using four stages, namely discovery and dream. Design, and destiny. The results of this community service are: a) the success of producing short films influenced by the enthusiasm and potential of the young Buddhist generation; the existence of competition means that the young Buddhist generation tends to have high creativity; b) short films act as an educational investment, where through training and making short films it opens up new insights and views, both from a technical perspective and the essence of the products produced. Their skills become intellectual capital for the younger generation, which can transform into other people. Short films become digital marketing tools, as the public can consume short film products produced in this community service program, and d) short films become the spirit of change in the era of digitalisation. 5.0, training and assistance in making short films for the young generation of Buddhists in Wonogiri as an effort to awaken the entrepreneurial spirit. Based on this, short film-making training has a positive impact on developing creativity and entrepreneurship for the young generation of Buddhists in Wonogiri.